Effective Qur'an Learning Strategies to Strengthen Children's Memorization with Zahrawain Method - Ari Kurniawati; M Muthoifin (Walidem Institute and Publishing (WIP), 2024)
The purpose of this study was to explore and evaluate the effectiveness of Qur'anic learning strategies using the Zahrawain Method in strengthening children's memorization. The research method used is qualitative research with a case study approach. The study participants consisted of a group of children who had started the process of learning the Qur'an with the Zahrawain method. Data was collected through observation, interviews, and analysis of documents related to the learning process. Data analysis was carried out using qualitative approaches, including thematic grouping and content analysis. The results showed that the use of the Zahrawain Method in learning the Qur'an was effective in strengthening children's memorization. This strategy can increase children's motivation and concentration in learning and memorizing verses of the Qur'an. In addition, the Zahrawain Method also helps to improve understanding and practical application of the contents of the Qur'an. These findings suggest that the application of the Zahrawain Method can be one of the effective strategies in Qur'an learning to strengthen children's memorization.